Microneedle-Assisted Transdermal Delivery of Lurasidone Nanoparticles - Ariana Radmard; Ajay K. Banga (MDPI AG, 2024)
Lurasidone, an antipsychotic medication for schizophrenia, is administered daily via oral intake. Adherence is a critical challenge, given that many schizophrenia patients deny their condition, thus making alternative delivery methods desirable. This study aimed to deliver lurasidone by the transdermal route and provide therapeutic effects for three days. Passive diffusion was found to be insufficient for lurasidone delivery. The addition of chemical enhancers increased permeation, but it was still insufficient to reach the designed target dose from a patch, so a microneedle patch array was fabricated by using biodegradable polymers. For prolonged and effective delivery, the drug was encapsulated in Poly (lactic-co-glycolic acid) (PLGA) nanoparticles which were made using the solvent evaporation method and incorporated in microneedles. Effervescent technology was also employed in the preparation of the microneedle patch to facilitate the separation of the needle tip from the patch. Once separated, only the needle tip remains embedded in the skin, thus preventing premature removal by the patient. The microneedles demonstrated robust preformation in a characterization test evaluating their insertion capacity, mechanical strength, and the uniformity of microneedle arrays, and were able to deliver a dose equivalent to 20 mg oral administration. Therefore, the potential of a transdermal delivery system for lurasidone using microneedles with nanoparticles was demonstrated.